Tinjauan Literatur : Interaksi Berbagai Faktor Risiko Gangguan Pendengaran Akibat Bising “Noise-Induced Hearing Loss” (NIHL) - Calista Putri Maharani; Trijayanthi Utama, Winda; Wardani, Nanda Fitri; Sutarto, Sutarto (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Noise-Induced Hearing Loss (NIHL) is one of the most prevalent occupational diseases worldwide, yet prevention efforts remain suboptimal. Traditional linear models focusing solely on noise intensity have failed to capture the multifactorial nature of this condition. This study is a narrative literature review aimed at analyzing the multifactorial interactions among biological, environmental, and behavioral factors contributing to NIHL. Literature was searched through PubMed, Scopus, ScienceDirect, and Google Scholar databases using inclusion criteria for studies published between 2010 and 2024. Of 86 identified articles, five key studies were selected for synthesis. The findings reveal that NIHL is primarily triggered by high-intensity noise exposure, further amplified by temporal characteristics of noise (kurtosis), combined exposure to dust or ototoxic chemicals, and modulated by age, work duration, and individual behaviors such as smoking and compliance with hearing protection. In conclusion, NIHL is best understood as the outcome of a multifactorial risk network, emphasizing the need for a paradigm shift toward holistic, personalized, and evidence-based prevention strategies. Keywords: Hearing Loss; Noisy, NIHL; multifactorial risk; literature review